Proceso de victimización de las mujeres del Cabildo Indígena Ambiká Etnia Pijao como consecuencia del desplazamiento forzado (2019)
This research paper describes the processes of victimization of the women of the Ambiká Ethnic Group of Pijao, who have been subjected to forced displacement, since they belong to one of the aboriginal peoples that has suffered the sociopolitical violence of the country, a fact that led to that affects occur in different areas of your life, which are particular to the rest of the population and other ethnic groups. For this purpose, the victimization phases of primary, secondary and tertiary victimization that make up the victimization process are deepened based on the subjective experiences of the participants.